2012
DOI: 10.2105/ajph.2012.300711
|View full text |Cite
|
Sign up to set email alerts
|

Risk Compensation: A Male Phenomenon? Results From a Controlled Intervention Trial Promoting Helmet Use Among Cyclists

Abstract: Prevention tools are challenged by risky behaviors that follow their adoption. Speed increase following helmet use adoption was analyzed among bicyclists enrolled in a controlled intervention trial. Speed and helmet use were assessed by video (2621 recordings, 587 participants). Speeds were similar among helmeted and nonhelmeted female cyclists (16.5 km/h and 16.1 km/h, respectively) but not among male cyclists (helmeted: 19.2 km/h, nonhelmeted: 16.8 km/h). Risk compensation, observed only among male cyclists,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…There is evidence of behaviour modification associated with helmet wearing in other studies. These have shown that regular helmet wearers decrease their cycling speed when not wearing a helmet [3], that male cyclists slightly increase speed in low speed areas when wearing a helmet [4], unhelmeted cyclists are more likely to commit a traffic violation [5], [6] and that some drivers believe helmet wearers cycling alone may behave more predictably than non-helmet wearers [7]. Despite Walker's hypothesis, there is no clear evidence helmet wearing leads to an increase in injury risk for the cyclist.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of behaviour modification associated with helmet wearing in other studies. These have shown that regular helmet wearers decrease their cycling speed when not wearing a helmet [3], that male cyclists slightly increase speed in low speed areas when wearing a helmet [4], unhelmeted cyclists are more likely to commit a traffic violation [5], [6] and that some drivers believe helmet wearers cycling alone may behave more predictably than non-helmet wearers [7]. Despite Walker's hypothesis, there is no clear evidence helmet wearing leads to an increase in injury risk for the cyclist.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion "Risk compensation, observed only among male cyclists, was moderate, thus unlikely to offset helmet preventive efficacy." [35].…”
Section: Bicycle and Motorcycle Helmetsmentioning
confidence: 99%
“…Risk compensation and bicycle helmets: A false conclusion and uncritical citations. Transportation Research Part F: Traffic Psychology andBehaviour, 58, 548-555. https://doi.org/10.1016/j.trf.2018.06.038 In this paper, we demonstrate how one of the rare experimental studies aimed at studying risk compensation and bicycle helmets arrives at a false conclusion (Messiah et al, 2012). It is, nevertheless, cited as evidence that helmeted (male) cyclists take more risks while riding a bike compared with those who ride without a helmet.…”
Section: Introductionmentioning
confidence: 72%
“…Risk compensation and bicycle helmets: A false conclusion and uncritical citations. Transportation Research Part F: Traffic Psychology andBehaviour, 58, 548-555. https://doi.org/10.1016/j.trf.2018.06.038 While we wait and call for more rigorous studies to examine possible risk compensation among those who voluntarily choose (and/or are 'forced' by legislation) to wear a bicycle helmet, we urge other researchers to stop citing Messiah et al (2012) as evidence of risk compensation. However, we are not very optimistic that this will actually happen, knowing that even retracted publications continue to be cited and in a positive context (Bar-Ilan & Halevi, 2017).…”
Section: Final Remarksmentioning
confidence: 99%